Cross-talk between bacterial two-component systems drives stepwise regulation of flagellar biosynthesis in swarming development - Wei, Chia-Fong; Tsai, Yu-Huan; Tsai, Sheng-Hui; Lin, Chuan-Sheng; Chang, Chih-Jung; Lu, Chia-Chen; Huang, Hsiou-Chen; Lai, Hsin-Chih (Biochemical and biophysical research communications, 2017)
Swarming motility is a mode of bacterial movement over a solid surface driven by rotating flagella in a coordinated manner. Bacteria can use two-component system (TCS), which typically comprises a sensor kinase and a specific cognate response regulator, to properly react to environmental changes. We previously showed that the TCS RssAB suppresses flagellar biosynthesis master regulator flhDC specifically in swarming lag phase to control surface migration timing without affecting expansion rate in Serratia marcescens swarming development. Here we demonstrate that the TCS QseBC, which has been found in several human pathogens involved in flagellar and virulence regulation, has cross-talk with RssAB. We demonstrate that the phosphorylated QseB repressed flhDC expression, reducing swarming migration rate with modest effect on migration initiation. Unexpectedly, the QseC can dephosphorylate non-cognate response regulator RssB. Deletion of qseC prolonged RssAB signaling, reduced flhDC expression, and delayed migration initiation. Our data suggest that QseC is a flagellar biosynthesis activator by de-repressing RssB ∼ P and QseB ∼ P respectively in lag and migration phases in a stage-specific manner in swarming development. [Display omitted] •QseB regulates swarming migration rate and flagellar biosynthesis in S. marcescens.•Phosphorylation of QseB is required for its binding to flhDC promoter.•QseC dephosphorylates RssB and deactivates RssAB signaling in swarming lag.